Effect of silver salt type on the physicochemical properties and antimicrobial activity of solid‐state Ag‐exchanged zeolites - Sajad Faryad; Mohammad Ghorbanpour; Majid Safajou‐Jahankhanemlou (International Journal of Ceramic Engineering & Science)
Abstract The silver‐exchanged zeolites were created using a solid‐state ion exchange method with silver sulfate and silver nitrate salts. Various techniques, including X‐ray diffraction (XRD), Brunauer–Emmett–Teller (BET) surface area analysis, scanning electron microscopy, and energy‐dispersive X‐ray spectroscopy, were employed to examine the structure, morphology, and physical‐chemical properties of the samples. The antimicrobial effectiveness of the zeolites was tested against gram‐negative Escherichia coli and gram‐positive Staphylococcus aureus, common bacteria found in wastewater. Before the silver exchange, the original zeolite exhibited small clustered particles, but after the exchange, its shape underwent significant transformation. The original clinoptilolite did not contain any silver, whereas the silver‐exchanged samples AgSSE6% and AgNSE6% had silver contents of 2.29% and 3.80%, respectively. The XRD analysis confirmed the presence of Ag and AgO within the structure of the exchanged clinoptilolite. BET analysis indicated that the incorporation of Ag ions into the zeolite structure through ion exchange led to a reduction in surface area and micropores volume. The research findings revealed that zeolites exchanged with silver were more effective in inhibiting the growth of S. aureus, compared to E. coli. Additionally, zeolites treated with AgSO4 exhibited a wider inhibition zone against both bacteria compared to zeolites treated with AgNO3.